PERFORMANCE ANALYSIS OF MADRASAH ALIYAH 1 STATE ISLAMIC SENIOR HIGH SCHOOL IN CREATING A TRANSPARENT AND ACCOUNTABLE SCHOOL IN GORONTALO - Suking, Arifin; Masaong, Abd Kadim; Buyuhi, Karimah (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2022)
Abstract: Madrasah are Islamic institutions with the responsibility to provide quality educational services to the community. This quality service can be seen from the school's performance. The purpose of this research is to identify; (1) learning management (2) school management and leadership in Madrasah Aliyah 1 State Islamic Senior High School in Gorontalo. This quantitative research is located in Madrasah Aliyah 1 State Islamic Senior High School in Gorontalo with 46 teachers as research subjects. Data collection techniques used are questionnaires and documentation. The collected data were analyzed using the percentage technique presented in the form of tables and diagrams.   The results showed that: (1) learning management obtained results of 81.02% including the effective category, and (2) the results of management and leadership management achievements obtained 87.84% including effective categories. Thus, it can be stated that the performance of Madrasah Aliyah 1 State Islamic Senior High School in Gorontalo is effective Keywords: madrasah performance, management, leadership